WHEN NATIONAL EXAMINATION NO LONGER DETERMINING GRADUATION, WILL STUDENTS ACCOMPLISH IT SERIOUSLY? - Retnawati, Heri; Hadi, Samsul; Munadi, Sudji; Hadiana, Deni; Muhardis, Muhardis; Apino, Ezi; Djidu, Hasan; Rafi, Ibnu; Yusron, Eri; Rosyada, Munaya Nikma (Indonesian Journal of Educational Assessment, 2019)
The National Examination in Indonesia, which began in 2015, was no longer a determinant of student graduation at the end of the education level. Utilization of the examination results will affect the seriousness of the students in working on it. This study aims to describe the level of seriousness of 12th grade students in working on National   Examinations, when it no longer a determinant of graduation by examining teachers and school principals’ point of view. This research is a qualitative study by using the phenomenology approach. Data was collected using focus group discussions (FGD) conducted 3 times in 3 provinces in Indonesia, consisted of Yogyakarta, South Kalimantan and East Nusa Tenggara. FGD participants were 9 high school principals, 9 vice principal of curriculum, and 54 teachers who teach subjects that are tested on national exam. In each province, three schools were selected, consisted of   two public schools, and one private school. Data were analyzed using data reduction stages, to find relationships between themes, and verification. The results showed that the motivation of 12th grade students in preparing National Examination were reduced.  They no longer focused on preparing the exams, otherwise they preparing themselves for higher education.  Furthermore, students tended to select subjects that were easier and the teacher should motivate students harder to prepare for the National Examination.